2005
DOI: 10.1253/circj.69.722
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Sauna Therapy Increases Arterial Endothelial Nitric Oxide Synthase Expression and Nitric Oxide Production in Cardiomyopathic Hamsters

Abstract: n patients with chronic heart failure (CHF), vascular resistance is increased through the activation of neurohumoral systems, such as the sympathetic nervous, renin-angiotensin and endothelin systems. 1 Vascular endothelial function, which is mainly represented by endothelium-dependent vasodilatory function through the production of vasodilators derived from the endothelium such as nitric oxide (NO), prostacyclin and endothelium-derived hyperpolarizing factors, is impaired in CHF and affects clinical symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
75
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 34 publications
4
75
1
3
Order By: Relevance
“…In particular, FIR may improve endothelial function, which is observed not only in animal studies (11,12,14) but also in one clinical study (13). Yu et al (11) suggested that the beneficial effect of FIR therapy on skin blood flow may be related to the l-arginine/nitric oxide (NO) pathway.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, FIR may improve endothelial function, which is observed not only in animal studies (11,12,14) but also in one clinical study (13). Yu et al (11) suggested that the beneficial effect of FIR therapy on skin blood flow may be related to the l-arginine/nitric oxide (NO) pathway.…”
Section: Discussionmentioning
confidence: 95%
“…In this respect, Akasaki et al (12) found that repeated FIR therapy could upregulate endothelial NO synthase (eNOS) expression and augment angiogenesis in an apolipoprotein E-deficient mouse model of unilateral hind limb ischemia. Moreover, Ikeda et al (14) reported that 4 wk of sauna therapy significantly increased the serum nitrate concentrations as well as the expression of mRNA and protein of eNOS in the aortas of TO-2 hamsters. In addition, Imamura et al (13) showed that 2 wk of repeated sauna therapy significantly improved vascular endothelial function, resulting in an increase in flow-mediated, endothelium-dependent dilation of the brachial artery from 4 to 5.8% in patients with coronary risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also indicated that skin temperature increased to a greater extent in females than in males following wet heat application. We consider this to reflect vasodilation of vessels due to excitation of water molecules resulting from release of preserved heat from the silicic acid gel of the hot pack and not the resonance phenomenon arising from subcutaneous fat [17][18][19] . However, multilateral measurement and analysis is needed for full understanding of this result 6) .…”
Section: Discussionmentioning
confidence: 99%
“…Wet heat application, such as repetitive saunas, can promote endothelial nitric oxide synthase (eNOS) activity and increase the levels of nitric oxide (NO). Therefore, water in an excited state can lead to strong vasodilatation 18) . Application of heat (43°C) also resulted in inhibition of apoptosis and modification of cell differentiation through the action of p38 mitogenactivated protein kinase (p38MAPK) and heat shock protein 27 (HSP27).…”
Section: Discussionmentioning
confidence: 99%